Age-related cognitive decline as a function of daytime testing. Issue 3 (4th May 2017) - Puiu, Andrei Alexandru
ABSTRACT: The current study investigates the effects of age, cognitive load, optimal time-of-day testing, and irrelevant background noise suppression on mental processing. One hundred and seventy-eight young ( M  = 22.97 years) and 114 old adults ( M  = 56.38 years) were assessed for implicit learning and speed of information processing under irrelevant sound interference early during daytime (7AM–2.30PM) or in the afternoons (3PM–midnight). No direct effect of irrelevant speech effect was found on implicit learning. An optimal time of testing per age group was identified according to the ability to suppress irrelevant auditory information. If no semantic meaning was derived from the sound conditions, irrelevant sound was easily inhibited leaving no room for declined cognitive performance. This suggests an intact phonological inhibition in older adults and a further circumvention of the phonological loop. However, when difficulty was increased, a widened performance gap between young and old people could be observed. Education modulated difficult performance irrespective of age. With increasing age, task demand fulfillment becomes a function of a limited time mechanism. If extraneous time is not adapted to cognitive skills and performance, higher order processing cannot be reached, rendering older adults slower than their younger counterparts.